MULTILINGUAL CODE-SWITCHING IN THE CLASSROOM: AN ANALYSIS FROM THE TEACHER’S NARRATIVE - Ramdhan Fathin Al Farabi, Muhammad; Hamamah, Hamamah; Muttaqin, Syariful (Premise: Journal of English Education and Applied Linguistics, 2024)
Code switching, the practice of alternating between languages in conversations, was of interest to researchers in sociolinguistics, especially in multicultural classrooms. This qualitative research utilized narrative interviews to explore code switching in the classroom, focusing on the teacher's narrative. Interviews were audio-recorded and supplemented with field notes. Data analysis involved narrative blocks. The research findings emphasized the effectiveness of multilingual code-switching and individualized instruction in enhancing students' English language learning. Embracing linguistic diversity, valuing students' native languages, and using creative learning approaches created a positive and inclusive environment, fostering comprehension, vocabulary retention, and cultural appreciation while motivating students. In conclusion, multilingual code-switching enhanced English learning by integrating native languages with instruction. Tailored teaching methods supported individual proficiency and learning styles, while creative code-switching boosted engagement and comprehension by linking English concepts to native languages.